Transformasi Pembelajaran Bahasa Arab Berbasis Artificial Intelligence untuk Meningkatkan Mahārah Lughawiyyah - Ilham Akbar; A Mustafa (PT. Nawa Edukasi Nusantara, 2026)
The digital transformation in education has driven significant innovation in language learning, including Arabic. The integration of Artificial Intelligence (AI) offers a more adaptive, interactive, and data-driven approach to enhancing language proficiency (mahārah lughawiyyah). This study aims to analyze the transformation of AI-based Arabic language learning and its impact on improving listening, speaking, reading, and writing skills. This research employs a qualitative approach using literature review and phenomenological analysis of AI-based learning practices in educational settings. Data were collected from reputable journal articles, research reports, and digital learning documentation. The findings indicate that AI significantly enhances learning effectiveness through personalized content, real-time feedback, and increased learner engagement. Technologies such as chatbots, speech recognition, and adaptive learning systems contribute substantially to improving Arabic communication skills. However, challenges remain, including limited infrastructure, teacher readiness, and digital literacy gaps. This study contributes a conceptual model for AI-integrated Arabic learning focused on developing comprehensive language skills.